Customer Satisfaction and Repeat Business are impacted by Product Quality and Services - Juliawan, Tri (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
To survive in the increasingly rapidly changing marketing world, companies are required to work harder, smarter and creative. The purpose of this study is to determine and analyze the effect of consumer satisfaction on consumer loyalty. The study was conducted using associative descriptive research methods. The population in this study is 1,569 consumers of Pintu Brand S-Plus at Mitra10 Cibubur as many as 1,569 consumers. The sample used was 319 respondents. The analytical tools used use descriptive statistical tests, classical assumption tests and hypothesis tests. The results of the study can be concluded that there is a positive and significant influence of Consumer Satisfaction on Consumer Loyalty showing the results of the tcount test = 12.592 while ttabel = 1.649 (tcalculate > ttable) with a significance level of 0.000 < 0.05, then in other words H0 is rejected and Ha is accepted.